The Effect of Addition of Vitamin E and Vitamin K on Growth and Survival of Giant Prawn (Macrobrachium rosenbergii) Larvae - Ni Nyoman Krisna Sanidhi Putri; Pande Gde Sasmita Julyantoro; Ni Luh Gede Rai Ayu Saraswati (Institute for Research and Community Services Udayana University (LP2M Universitas Udayana), 2024)
Giant prawn (Macrobrachium rosenbergii) is a potential fishery commodity. Recently, the commercial aquaculture of giant prawn has developed quite rapidly, especially in the rearing sector, due to its high economic value and accessible cultivation technology application. Low survival and growth are the causes of delays in the cultivation of giant prawns. The quality of the food for giant prawns is important to support the survival of the prawns during aquaculture activities. This study looks at how adding vitamins E and K to artificial food affects the growth and survival of giant prawn larvae from the Galah Prawn Seed Center (BBUG) in Klungkung, Bali. The results show that vitamin E had the highest influence on the growth and survival of giant prawn larvae, with 35.55% survival and a 4.727 growth index. Meanwhile, vitamin K in the prawn feed has no effect due to poor water quality and high mortality. The range of measured water quality was temperature (26-31°C), pH (7.5-7.8), and salinity (5-20 ppt). In general, this study shows that vitamin E had a positive effect on the growth and survival of giant prawn larvae.